(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): To identify the common psychosocial effects of infertility among the childless couples of Bangladesh. Materials and Methods: This cross sectional quantitative survey was conducted at a tertiary level fertility center in Dhaka, Bangladesh from November 14, 2012 to November 30, 2012. Respondents were chosen by judgment sampling. Only the couples without any child were chosen for interview. Sixty-six couples were interviewed and three couples refused who came for treatment at the center. Primary data was collected from the respondents with preformed questionnaire. Informed written consent was taken before the interview, from both partners or only one partner where the other was absent Results: The mean ages of the men were 36 years and women were 28 years. The mean age for age at marriage of men and women were 29 and 22 respectively. Among the psychological effects, stress and anxiety were common in both men and women. Family problems were found less among the respondents. Only significant one that was found in both men and women was the pressure from family members, which was found in about one third of the respondents. Social effects were not found among half of the respondents. The other half avoided family gatherings (16%), meeting friends (13%), social gatherings (10%) and 15% respondents said that they do not like to go out at all. Conclusion: The psychosocial effects of infertile couples can lead to depression, frustration and sometimes aggression making them dysfunctional social beings. It also decreases work productivity and quality of life. Necessary preventive measures should be taken through appropriate public health interventions like patient counseling, awareness campaign etc. to avoid the psychosocial consequences. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 28-33